S35. THE PLACEBO CONUNDRUM: MITIGATING THE RESPONSE AT THE SITE LEVEL. (18th May 2020) - Hassman, Howard; Cohen, Elan; Walling, David; Wyka, Katarzyna; Grindell, Vera; Glass, Steven; Ball, Roberta; Styczynski, John; Lobb, Jaclyn; Hazzard, Dakota; Joseph, Ashok; Ereshefsky, Larry
Abstract: Background: The placebo effect within Schizophrenia clinical trials has been noted as alarmingly high (Kinon et al., 2011). While numerous methodological approaches have been implemented to reduce this phenomenon (e.g., centralized ratings, remote rater monitoring, and data surveillance before subject randomization), research indicates the placebo effect is increasing over time (Chen et al., 2010). This may be because there has been no intervention aimed to minimize the placebo effect specifically targeting both the study subject and site staff. This is surprising given that the primary 'culprits' of the effect are from both individuals. The Placebo-Control Reminder Script (PCRS) was explicitly developed to help rectify this problem as it simultaneously educates subjects and reminds site raters (who are crucial in assessing symptoms which ultimately determine drug-placebo separation) of the key factors most cited as inducing these effects or Placebo Response Factors (PRFs – participant expectations of benefit, lack of placebo understanding, misconception of expected interactions with research site staff, and subject role uncertainty; Alphs et al., 2012). The current study explored the efficacy of the systemically designed PCRS in helping to reduce the placebo effect among subjects with a primary psychotic diagnosis. Methods: Across two US sites, Schizophrenia / Schizoaffective adult patients experiencing at least moderate depression, per the self-reported Beck Depression Inventory-II (BDI-II; Beck et al., 1996), were randomized into two groups (70% of enrolled subjects per site were required to have a Schizophrenia diagnosis). The Intervention Group (IG) was read at each of the three study visits the one-page, brief (2 minute) PCRS before the BDI-II was administered, whereas the Control Group (CG) was not read the PCRS. Subjects' perceptions of improvement regarding their depressive symptoms were also collected. Depression, and not psychosis, was the dependent variable due to a combination of scale psychometric limitations (e.g., the lack of targeted self-report psychosis measures) and psychosis assessment length and duration. All subjects were informed via the Informed Consent Form there was a 50% chance of receiving placebo or active drug developed to improve their depressive symptoms, but all subjects received placebo. Given this deception, subjects received a Debriefing Form at the end of the study revealing the investigation's true intent and procedures. Results: As expected, IG (n=23) and CG (n=23) subjects did not differ in baseline characteristics, including depression (BDI-II: IG M=24.09, SD=2.39 vs. CG M=24.48, SD=3.37; p=.651) and diagnosis of either Schizophrenia or Schizoaffective Disorder (all p>.05). As hypothesized, time-by-group interaction showed that compared to the CG, IG subjects reported significantly (p=0.002) higher BDI-II scores at the endpoint visit (IG M=22.00, SD= 5.17 vs. CG M=17.17, SD=5.63), and perceived themselves as less improved in their sadness/depression (p=.013). Discussion: The findings indicate that providing education at every study visit focusing on PRFs seems to significantly manage the placebo effect among participants with a primary psychotic diagnosis. Additionally, given that the PCRS helped subjects report continued depressive symptoms while in fact on a placebo (i.e., they described their depression more accurately) than subjects who were not read the PCRS, the current results have implications for the valid use of patient-reported outcome measures in clinical trials when the PCRS, or similar script, is administered. Other methodological ramifications as well as study limitations will be discussed in the poster.